The bendamustine plus rituximab regimen is active against primary nodal marginal zone B‐cell lymphoma. Issue 4 (22nd July 2016) - Laribi, Kamel; Tempescul, Adrien; Ghnaya, Habib; Denizon, Nathalie; Besançon, Anne; Anghel, Andreea; Farhi, Jonathan; Truong, Catherine; Lemaire, Pierre; Poulain, Stephanie; Bolle, Delphine; Ianotto, Jean Christophe; et al.
Abstract: Primary nodal marginal zone lymphoma (NMZL) is a rare disease. There is no current consensus on how to treat it. The bendamustine plus rituximab (BR) regimen is effective for the treatment of follicular and other indolent lymphomas, but its efficacy in NMZL is not known. We analyzed the outcome of 14 patients diagnosed with NMZL (median age 67 years) who were treated with 375 mg/m 2 of rituximab on day 1 and 90 mg/m 2 of bendamustine on days 1 and 2. The overall and complete response rates were 93% and 71%, respectively. Major toxicity (grade 3/4 neutropenia) occurred in 5% of treatment courses. After a median follow‐up of 22 months (range: 18‐55), the overall survival and the free survival rates were 100% and 93%, respectively. None of the patients showing a complete or partial response developed secondary myelodysplastic syndrome/acute myeloid leukemia. Bendamustine plus rituximab was found to be an active and well‐tolerated regimen leading to the rapid control of disease.